1.56-to-2.84 μm SRS conversion of chirped pulses of a high-power erbium fibre laser in a methane-filled hollow-core revolver fibre. (1st March 2022) - Krylov, A.A.; Gladyshev, A.V.; Senatorov, A.K.; Kolyadin, A.N.; Kosolapov, A.F.; Khudyakov, M.M.; Likhachev, M.E.; Bufetov, I.A.
Abstract: Single-cascade 1.56-to-2.84 μm SRS conversion is demonstrated in a hollow-core revolver fibre filled with methane at a pressure of 25 atm under pumping by positively chirped pulses of a high-power erbium-doped all-fibre laser. At a maximum pump pulse energy of 34 μJ (average power 3.74 W) and a pump pulse duration of about 260 ps, ultrashort pulses (USPs) with a duration of 110 ps and an energy of 1.33 μJ (average power 133 mW) are achieved at the centre wavelength of 2.84 μm. The gas fibre Raman lasers based on hollow-core fibres with pumping by high-power fibre sources are promising for producing all-fibre systems emitting USPs in the mid-IR range.